Pengaruh Reputasi Lembaga dan Financial Technology Crowdfunding Terhadap Keputusan Berdonasi di Dompet Al-Qur'an Indonesia - Sa'diyah, Halimatus; Yunita Ardilla (Journal of Islamic Management, 2024)
In the world of philanthropy and non-profit institutions, donations are one of the crucial factors in determining the sustainability of the institutions. Of course, the decision to donate is one of the efforts to be considered, along with the factors that drive that attitude. This research aims to understand the factors that drive community decisions to give donations to philanthropic and non-profit organizations. Using quantitative approaches and SPSS analysis, the research involves research instruments, classical assumption tests, double linear regression, model accuracy evaluation, T tests, and data processing processes. The research findings confirm that both the reputation of institutions and crowdfunding financial technology significantly influenced donation decisions in the Qur’an Wallet, with both together having an impact of 49.9%.